How the use of music and movement impacts the learning of reading skills by preschoolers (IR) - Augustine, Christine (2013)
How the Use of Music and Movement Impacts the Learning of Reading Skills by Preschoolers. Christine Augustine, 2013: Applied Dissertation, Nova Southeastern University, Abraham S. Fischler School of Education. ERIC Descriptors: Music, Preschool Education, Literacy, Reading Skills, Gender Preschool years are considered the "prime time" for children to develop physical, social, cognitive, and language development. The most critical issue in current education is the poor development of reading skills among children. It is proved that integrating music into children's daily activities promotes literacy development, particularly with English language learners. Unfortunately, music is not emphasized in Malaysian government preschools as music teachers lack knowledge and teaching skills. The purpose of this study was to assess the effect of music and movement on the reading skills of 40 fiveyear- old preschoolers at a university preschool. This study sought to evaluate three reading skills or subtests- Print Knowledge, Definitional Vocabulary, and Phonological Awareness. The intervention was comprised of musical activities that included songs or singing nursery rhymes and body movements. This quasi-experimental design utilized the Test of Preschool Early Literacy that measures early literacy skills for preschoolers. The results showed that music and movement activities impacted preschoolers in the overall reading skills (p = .02), print knowledge (p = .005), and definitional vocabulary (p = .03) after the intervention but did not impact the phonological awareness skills (p = .18). These findings confirmed that music and movement enhanced literacy skills for a duration of 6 weeks. Many opportunities should be included for children so they can be thoroughly engaged in music and literacy activities. Teachers should be equipped with sufficient skills and knowledge